THE ENGLISH SCANNING SKILL OF BILINGUAL AND MONOLINGUAL TOURISM STUDENTS IN DENPASAR TOURISM ACADEMY - Risadi, Md. Yudyantara; Astawa, I Gede; Winia, I Made; Laba, I Nengah (Journal of Business on Hospitality and Tourism, 2020)
This study aimed at figuring out the access of Indonesian students to English and figuring out the difference of scanning skill possessed by bilingual students and monolingual students. The subject of this study was 31 2nd semester students from Denpasar Tourism Academy, Bali. The data was collected through a questionnaire and a provided test. The result of the questionnaire shows that students have more access to English through films, listening to English songs, computer games and their mobile phone when they are chatting. From the questionnaire is also found that 42% of the students were monolingual -they use Bahasa only at school and at home- and 58% of the students were bilingual –they use Bahasa and local language-. The result of the test shows that students who are monolingual in that school outperform the bilingual with the average score is 78.00, meanwhile the bilingual students have the average score with score 64.00. It implies that the monolingual students can answer easily the questions given by the teacher than the bilingual students because the use of Bahasa Indonesia only helps them to understand the instruction